PENGARUH PLACE BRANDING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG (Studi Pada Pengunjung Lasem Kota Tua/ Pecinan di Rembang) - Ndomatul Khabibah; Anik Lestari Andjarwati (STKIP Persada Khatulistiwa Sintang, 2022)
Tourism is a trip carried out repeatedly, both planned and unplanned, taking place temporarily to fill pleasure, curiosity, spending holidays or other things. An attractive tagline also makes potential visitors curious about the tours they will visit. Potential visitors prefer to find information through the internet and pay attention to positive and negative comments from other visitors in deciding to visit. This paper aims to study the relationship between place branding, electronic word of mouth, and tourists' decisions to visit. This study focused on tourists visiting Tiongkok Kecil Heritage Lasem. The data analysis technique was multiple linear regression. The results showed that place branding and electronic word of mouth had a positive and significant effect on visiting decisions. The implications of this research can be used as input for Tiongkok Kecil Heritage Lasem in developing place branding